2010
DOI: 10.1002/art.27616
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin‐mediated changes in effector cells involved in the pathophysiology of rheumatoid arthritis

Abstract: Objective. Rheumatoid arthritis (RA) is associated with increased production of adipokines, which are cytokine-like mediators that are produced mainly in adipose tissue but also in synovial cells. Since RA synovial fibroblasts (RASFs), lymphocytes, endothelial cells, and chondrocytes are key players in the pathophysiology of RA, this study was undertaken to analyze the effects of the key adipokine adiponectin on proinflammatory and prodestructive synovial effector cells.Methods. Lymphocytes were activated in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 46 publications
(67 reference statements)
3
86
0
Order By: Relevance
“…However, this stimulatory capacity of adiponectin is not restricted to RASFs. In endothelial cells, chondrocytes and lymphocyte subpopulations, proinflammatory factors, and chemokines were also induced by adiponectin (36). Additionally, adiponectin increased the expression of MMPs in chondrocytes and that of adhesion molecules in endothelial cells (36).…”
Section: Adiponectin In Ramentioning
confidence: 96%
See 3 more Smart Citations
“…However, this stimulatory capacity of adiponectin is not restricted to RASFs. In endothelial cells, chondrocytes and lymphocyte subpopulations, proinflammatory factors, and chemokines were also induced by adiponectin (36). Additionally, adiponectin increased the expression of MMPs in chondrocytes and that of adhesion molecules in endothelial cells (36).…”
Section: Adiponectin In Ramentioning
confidence: 96%
“…In endothelial cells, chondrocytes and lymphocyte subpopulations, proinflammatory factors, and chemokines were also induced by adiponectin (36). Additionally, adiponectin increased the expression of MMPs in chondrocytes and that of adhesion molecules in endothelial cells (36). Thus, adiponectin exerts proinflammatory and prodestructive properties in the majority of cells involved in cartilage destruction in RA.…”
Section: Adiponectin In Ramentioning
confidence: 96%
See 2 more Smart Citations
“…It promotes inflammation through increased TNF␣, IL-6, IL-8, and RANTES secretion by human primary lymphocytes. Likewise, it induces IL-6, IL-8, growth-related oncogene ␣, MCP-1, and RANTES secretion by human macrovascular endothelial cells (97). On the contrary, Lee et al have reported in mice that adiponectin mitigates the severity of collagen-induced arthritis (98).…”
Section: Adiponectin and Rheumatic Diseasesmentioning
confidence: 99%